Escapable law - Green, L (Oxford University Press, 2019)
The law tells us what we ought to do, legally speaking. Why care about that? We usually have moral reasons to care about what the law thinks since we need to know whether its demands are justified. We often have prudential reasons since those charged with applying and executing law can make trouble for us. We sometimes have role-based reasons to care: it may be our job or station to teach, study, or apply legal norms. Moreover, a few people have reasons of personal taste or interest—they are the kind of people that find the law and its ways intrinsically interesting. All these reasons and others...